2003
DOI: 10.1136/sti.79.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Absence of hepatitis C virus transmission in a prospective cohort of heterosexual serodiscordant couples

Abstract: Objective: To analyse hepatitis C virus (HCV) transmission in a cohort of heterosexual couples who are discordant both for HIV and for HCV. Methods:We followed an open cohort of 171 people, 152 women and 19 men, who were not initially infected by either HIV or HCV, and whose steady heterosexual partner presented antibodies to both viruses (index case). Other risk exposures were excluded. Every 6 months clinical, epidemiological, and risk behaviour information was collected, and antibodies to both viruses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 17 publications
2
80
1
Order By: Relevance
“…However, the majority of studies mention rates of between zero and 3%. These low indexes, associated with rare risk factors, suggest that sexual transmission presents a minimal or negligible risk 18,30,31,44,49,51,54,69,82,83,92 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the majority of studies mention rates of between zero and 3%. These low indexes, associated with rare risk factors, suggest that sexual transmission presents a minimal or negligible risk 18,30,31,44,49,51,54,69,82,83,92 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of studies mention rates of between zero and 3%. These low indexes, associated with rare risk factors, suggest that sexual transmission presents a minimal or negligible risk 18,30,31,44,49,51,54,69,82,83,92 .Studies that discuss specific groups, such as those who attend clinics for sexually transmitted diseases like drug abusers, homosexuals and sex workers, reveal findings that differ from those of the general population, and the risks of sexual transmission of HCV increase considerably 12,15,18,23,25,26,37,51,61,65,68,69,83,85,91 . …”
mentioning
confidence: 96%
See 1 more Smart Citation
“…A historical series of risk factors identified for acute HCV hepatitis in the United States from 1986 to 1996 clearly show a marked drop of transfusions and an elevated curve of sexual exposure in the absence of other known risk factors [7]. Most studies focusing on stable heterosexual couples, however, found a 0-3% risk of transmission from an infected partner to the other [8][9][10][11][12]. Therefore, many authors argument that sexual contact brings a minimal or negligible risk of transmission.…”
mentioning
confidence: 99%
“…Percutaneous exposure of health care workers to blood from coinfected patients was also shown to increase the risk of acquiring HCV [40]. Sexual transmission of HCV is rare even to partners of co-infected patients [44].…”
Section: Route Of Transmissionmentioning
confidence: 99%